Bewegungsförderung bei Frauen in schwierigen Lebenslagen - das BIG-Projekt - Herbert, Annika; Abu-Omar, Karim; Streber, Anna (Public Health Forum, 2019)
There are various barriers that often prevent women in difficult life situations from engaging in at least sufficient levels of physical activity. The BIG project was developed as a community-based participatory project to improve physical activity among disadvantaged women. BIG has been successful by providing exercise classes tailored to the needs of women, empowering women by having them take part in planning processes, building community level capacity, and initiating policy and environmental changes for health promotion on the community level.
CRIS-Team Scopus Importer:2019-07-12
Keywords: capacity building; community setting; participation; physical activity promotion among women in difficult life situations; tailored programs

Bewegungsförderung bei Menschen in schwierigen Lebenslagen - Fleuren, Tobias; Herbert-Maul, Annika; Linder, Stephanie; Geidl, Wolfgang; Reimers, Anne Kerstin; Abu-Omar, Karim (Bewegungstherapie und Gesundheitssport, 2020)
Der vorliegende Artikel beschäftigt sich mit der Bewegungsförderung bei Menschen in schwierigen Lebenslagen und den besonderen Herausforderungen, die an eine erfolgreiche Umsetzung entsprechender Programme und Interventionen für diese Personengruppen gestellt werden. Anhand zweier Praxisbeispiele wird aufgezeigt, wie Bewegungsförderung für schwer erreichbare Adressat*innen durch partizipative Ansätze gelingen kann. Das BIG-Projekt (Bewegung als Investition in Gesundheit) bietet einen Ansatz für Frauen in schwierigen Lebenslagen. Bei GESTALT (GEhen, Spielen und Tanzen Als Lebenslange Tätigkeiten), einem Bewegungsprogramm zur Demenzprävention, werden Personen ab 60 Jahren adressiert, die bislang nur unzureichend oder gar nicht körperlich aktiv sind. Damit solche Projekte auf möglichst viele neue Kommunen übertragen werden können, muss die bisherige enge wissenschaftliche Begleitung durch mehr Verantwortung und Eigenständigkeit in den Kommunen ersetzt werden. Für die Praxis der Bewegungsförderung bedeutet dies, dass eine Erweiterung von Ausbildungsinhalten in Betracht gezogen werden sollte, um die notwendigen Kompetenzen und Strategien zu vermitteln, damit schwierige Zielgruppen adäquat erreicht werden.<br
Keywords: Bewegungsförderung; Partizipation; Menschen in schwierigen Lebenslagen

Corrigendum: “For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women(Front. Public Health, (2022), 10, (867626), 10.3389/fpubh.2022.867626) - Sauter, Alexandra; Herbert-Maul, Annika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Frahsa, Annika; Linder, Stephanie; Herrmann-Johns, Anne (Frontiers in Public Health, 2023)
In the original published article, a data reanalysis is included which relates to a physical activity promotion project that has been running at various sites in Germany since 2005. The qualitative data used for the published reanalysis was collected between 2007 and 2011. A detailed description of the data set used and the reanalysis we conducted can be found in the methods section of the published article. In the published article, Roger, Rutten, Frahsa, Abu- Omar and Morga (2011) was cited three times. The corrigendum now includes further references to the work of Roger et al. (2011) and new to Rutten et al. (2008) in the introduction, method, and discussion sections of our paper.
CRIS-Team Scopus Importer:2023-03-17
Keywords: community-based participatory research; empowerment; ethnic minority; health promotion; low socioeconomic status; physical activity; qualitative research; women's health

Entwicklung eines Fragebogens zur Messung der kommunalen Kapazitäten für partizipative Bewegungsprogramme: eine Think-aloud-Studie - Till, Maike; Abu-Omar, Karim; Streber, Anna; Fleuren, Tobias; Herbert-Maul, Annika; Reimers, Anne Kerstin; Ziemainz, Heiko (Prävention und Gesundheitsförderung, 2023)
Background: Communities are of crucial importance for health promotion and the prevention of diseases. Local capacities are especially important for the successful implementation of health promotion projects and for reaching the target population. When considering the scale-up of projects with a focus on physical activity promotion (BIG and GESTALT) in the community setting, it is of great importance to develop a tool that can measure those capacities. Objectives: A questionnaire for the pragmatic measurement of capacities through local authorities was developed, tested, and revised within a think-aloud study. Methods: Based on empirical evidence, we developed a capacity questionnaire which was completed by six project coordinators during a think-aloud study. Data was analyzed using qualitative content analysis and the response-process-theory. Following the analysis, the questionnaire was adapted. Results: Participants mentioned a total of 81 errors in four categories, which had been adjusted: 1) comprehension, 2) retrieval, 3) judgement, 4) response. The final questionnaire comprises 63 questions in six areas: participation, local leadership, available resources, networking and cooperation, health care, and BIG-specific questions. Conclusion: The questionnaire provides physical activity promotion projects with the opportunity to pragmatically measure capacities in the community setting.
Created from Fastlane, Scopus look-up
Keywords: Capacity development; Community Development; Participation; Physical activity promotion

“For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women - Sauter, Alexandra; Herbert-Maul, Annika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Frahsa, Annika; Linder, Stephanie; Herrmann-Johns, Anne (Frontiers in Public Health, 2022)
Introduction: Community-based participatory research (CBPR) is an effective health promotion approach for reaching socially disadvantaged groups. However, there is limited evidence on how such interventions and their effects can be reproduced across time and place. The present study examines the effects of BIG (i.e., movement as an investment in health), a long-standing German CBPR project. Since 2005, BIG has aimed to empower women in difficult life situations to increase control over their health determinants and reduce social inequalities by promoting physical activity. One of BIG's key features is its implementation in several German municipalities since 2005. This study explores (a) whether participation could change women's empowerment, and (b) how increased empowerment affects other areas of women's lives. Methods: With a total of 63 interviewees (i.e., 40 participating women, 7 trainers, 3 project coordinators, and 13 stakeholders), we conducted 53 semi-structured qualitative interviews in five BIG communities between 2007 and 2011. Some interviews were conducted with two people simultaneously. The interview guide contained questions on various dimensions of empowerment (e.g., project engagement, increased self-efficacy, and developed competencies). Framework analysis was used for the analytical process. Results: BIG contributed to women's empowerment in various ways, including increased self-efficacy, social network promotion, competency development, and increased motivation to change physical activity behavior. Women who took on added tasks and became more involved in project planning also strengthened their organizational empowerment. Furthermore, increased empowerment had a positive influence on the women's quality of life, family, and professional lives. Conclusion: The novel findings helped in understanding the effects of a complex empowerment-based approach that promoted physical activity among women in difficult life situations. Future research should focus on the long-term effects of these programs and their transferability to other sites. Further effort is necessary in the area of public health policy.
CRIS-Team Scopus Importer:2022-08-26
Keywords: community-based participatory research; empowerment; ethnic minority; health promotion; low socioeconomic status; physical activity; qualitative research; women's health

„Gesundheit für alle im Stadtteil“ – ein kommunaler Ansatz zur Gesundheitsförderung in sozial benachteiligten Stadtteilen Nürnbergs. - Barth, Janina; Mengel, Michael; Seebaß, Katharina; Retzlaff, KN; Herbert-Maul, Annika; Barthel-Kraus, E; Wiemer-Urtube, Silvina (Praxishandbuch Qualitätsentwicklung und Evaluation in der Gesundheitsförderung, 2019)
Keywords: Chancengleichheit

Präventionsdilemma auf kommunaler Ebene? - Herbert-Maul, Annika; Abu-Omar, Karim; Till, Maike; Fleuren, Tobias; Wolff, Andrea R.; Reimers, Anne Kerstin (Prävention und Gesundheitsförderung, 2022)
Health promotion often benefits mainly socially privileged persons, while disadvantaged people are reached less often. It remains an important question whether the same holds true for the recruitment of communities to take part in health promotion projects. Objectives Based on two Bavarian projects for community-based physical activity promotion, this study examines whether socioeconomically disadvantaged communities with low health promotion structures are being reached to apply for project funding and which factors influence their readiness to participate. Methods Data on population level indicators and socioeconomic disadvantages of 171 communities are compared for participating/interested communities and disadvantaged communities. By means of a systematic internet search, health promotion activities of selected communities are analyzed. Barriers and facilitating factors for the implementation of the two projects are recorded through a document analysis. Results The participating and interested communities have larger populations, are less disadvantaged, and provide more health promotion offers than disadvantaged communities. Financial factors, political support, and committed leadership have a large influence on participation. Discussion The results of this study point to an inequality paradox for preventive actions on the community level. In order to prevent health inequalities between communities, disadvantaged communities might need to be involved in the design of funding programs in order to tailor these programs to their needs and thus make it easier for them to acquire project fundin
Keywords: Background; Community-based health promotion; Community readiness; Socioeconomic deprivation; Funding programs; Participation

Preferences of women in difficult life situations for a physical activity programme: protocol of a discrete choice experiment in the German NU-BIG project - Pedron, Sara; Herbert-Maul, Annika; Sauter, Alexandra; Linder, Stephanie; Sommer, Raluca; Vomhof, Markus; Gontscharuk, Veronika; Abu-Omar, Karim; Thiel, Ansgar; Ziemainz, Heiko; Holle, Rolf; Laxy, Michael (BMJ Open, 2023)
Introduction The BIG project ('Bewegung als Investition in die Gesundheit', ie, 'Movement as Investment in Health') was developed in 2005 as a community-based participatory research programme to offer accessible opportunities for physical activity to women in difficult life situations. Since then, the programme has been expanded to eight sites in Germany. A systematic evaluation of BIG is currently being conducted. As part of this effort, we strive to understand the preferences of participating women for different aspects of the programme, and to analyse their willingness to pay. Methods and analysis In this protocol, we describe the development and analysis plan of a discrete choice experiment (DCE) to investigate participants' preferences for a physical activity programme for women in difficult life situations. The experiment will be embedded in a questionnaire covering several aspects of participation in the programme (eg, reach, efficacy and further effects) and the socioeconomic characteristics of all active participants. After a thorough search of the literature, BIG documents review and expert interviews, we identified five important attributes of the programme: course times, travel time to the course venue, additional social activities organised by BIG, consideration of wishes and interests for the further planning of courses and costs per course unit. Thereafter, we piloted the experiment with a sample of participants from the target group. After data collection, the experiment will be analysed using a conditional logit model and a latent class analysis to assess eventual heterogeneity in preferences. Ethics and dissemination Understanding women's preferences will provide useful insights for the further development of the programme and ultimately increase participation and retention. The questionnaire, the included DCE and the pretest on participants received ethical approval (application no. 20-247-1-B). We plan to disseminate the results of the DCE in peer-reviewed journals, national conferences and among participants and programme coordinators and organisers.
CRIS-Team Scopus Importer:2023-07-28
Keywords: HEALTH ECONOMICS; SOCIAL MEDICINE; SPORTS MEDICINE

Promoting physical activity among socially disadvantaged women: Findings on target group outreach, course retention, and impact of the BIG project as a case study for participatory interventions in community settings Bewegungsförderung bei sozial benachteiligten Frauen: Erkenntnisse zur Zielgruppenerreichung, Kursbindung und Wirkung des BIG-Projekts als Fallstudie für partizipative Interventionen im kommunalen Setting - Linder, Stephanie; Herbert-Maul, Annika; Ziemainz, Heiko; Thiel, Ansgar; Holle, Rolf; Laxy, Michael; Pedron, Sara; Abu-Omar, Karim (German Journal of Exercise and Sport Research, 2023)
Background: The BIG project—a participatory project in a community setting (“Bewegung als Investition in Gesundheit”)—was developed in 2005 to facilitate access to physical activity for disadvantaged women. Since then, BIG has been transferred to 17 municipalities. Aim: To investigate whether socially disadvantaged women can be reached and retained in exercise classes in the BIG project. In addition, the information provided by the women on their state of health and exercise is reported. Finally, we will examine whether five risk factors associated with social disadvantages are associated with health status and physical activity. Methods: Quantitative cross-sectional data from six survey waves (2006–2013) from two project sites (Erlangen, Regensburg) were summarized. To analyze the reach of the target group, participant characteristics (N = 430) were compared with population data from the sites. The reach of the target group, course retention, and data on health status and physical activity were also descriptively analyzed. The influence of risk factors and physical activity on health status was examined by multivariate regression analyses. Results: Of the participants, 67% had at least one risk factor. Women participated in the BIG courses for a mean of 2.4 years. Over 50% of women reported improved health, and over 60% exercised more compared with before BIG. The number of risk factors present was associated with the health status compared to the time before BIG (p < 0.001). Lack of German language skills showed a significant association with current health status. Conclusions: The BIG project reaches socially disadvantaged women. In particular, women with few risk factors report positive change in health status and physical activity compared to the time before BIG participation. Here, the number of risk factors present and lack of German language skills seem to be important.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Health promotion; Participation; Physical activity promotion; Socioeconomic disparities in health; Target group reach

Scaling up a community-based exercise program for women in difficult life situations in Germany—The BIG project as a case-study - Herbert-Maul, Annika; Abu-Omar, Karim; Streber, Anna; Majzik, Zsuzsanna; Hefele, Jeanette; Dobslaw, Stephanie; Werner, Hedi; Wolf, Alexandra; Reimers, Anne Kerstin (International Journal of Environmental Research and Public Health, 2021)
Scaling up community-based participatory research (CBPR) remains challenging. This case-study reports on how, and under which conditions, a CBPR project aiming at promoting exercise among socially disadvantaged women (BIG) scaled up at four project sites. As part of BIG, researchers support city administrations in implementing a participatory project to reach socially disadvantaged women for exercise. The case study was conducted in winter 2020 in southern Germany and is based on a co-creative process involving city administrators and researchers. Following Kohl and Cooley’s scaling up dimensions, scaling up BIG was investigated at the four sites using a mixed-method approach. Course registrations and offers were analysed, and qualitative interviews (n = 4) with administrative staff members were conducted and analysed using content analysis. The geographical coverage of exercise classes, the addressed groups, and the utilisation of participatory methods by city administrations are described. All four sites managed to scale-up project activities. Three of the four sites reported that further growth of the project was no longer possible due to limited resources. All sites attempted to reach a larger number of, and more diverse, women. One site managed to scale-up the use of participatory methods within the city administration. The following important facilitators for scaling up CBPR projects were reported: advertisements tailored to the needs of the addressed women, utilising participatory approaches, and equipping project coordinators with sufficient resources.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Ethnic minority; Exercise; Health promotion; Low socioeconomic status; Physical activity; Refugees; Scaling up; Socially disadvantaged groups

Scaling Up Physical Activity Promotion Projects on the Community Level for Women in Difficult Life Situations and Older People: BIG-5 and GET-10—A Study Protocol - Till, Maike; Abu-Omar, Karim; Herbert-Maul, Annika; Fleuren, Tobias; Reimers, Anne Kerstin; Ziemainz, Heiko (Frontiers in Public Health, 2022)
Introduction: Physical inactivity is a major risk factor for a population's health, especially among socially disadvantaged groups. Many health promotion projects focus on increasing physical activity among their respective target groups. However, because they are mostly developed and implemented under laboratory conditions, they fail when being scaled to real-world settings. The community-based participatory research projects BIG and GESTALT have demonstrated their effectiveness regarding the physical activity promotion in real-world settings by employing a participatory method. Material and Analysis: Within the context of the BIG-5 and GET-10 projects, these previously implemented and tested participatory projects are scaled to 15 additional settings in Bavaria, Germany. By applying an overarching mixed-methods evaluation framework, the aim is to gain insights into a) the recruitment of communities for scale-up; b) the specific results of the projects according to the RE-AIM framework. In the recruitment of communities, standardized information on the first contact, the consultation process, the person in charge, and previously implemented health promotion projects are collected. A systematic web search will complete information on each community and their health promotion activities. Results will be compared with information on those communities most in need, here according to the deprivation index of communities in Bavaria, Germany. The scale-up process and its results will be measured using semi-structured interviews with project coordinators. A standardized questionnaire will be used with the course's participants. Applying the RE-AIM framework, the collected data will be analyzed deductively. Discussion: We expect the results to be highly relevant for the effective scale-up of any health promotion project. The study will enhance the understanding of how to reach those communities most in need of health promotion projects and will identify the barriers coordinators face in reaching socially disadvantaged groups. Conclusion: Although participatory projects are often used as individual projects, little is known about the scaling up of participatory health promotion projects. This cross-cutting evaluation of two projects aims at producing data on the barriers and facilitators for the reach of settings most in need, and those success factors for a durable implementatio
Keywords: scale-up; socially disadvantaged; physical activity; community-based participatory research; low socioeconomic status; ethnic minoritie; vulnerable groups

The long-term public health impact of a community-based participatory research project for health promotion among socially disadvantaged women—a case study protocol - Abu-Omar, Karim; Ziemainz, Heiko; Loss, Julika; Laxy, Michael; Holle, Rolf; Thiel, Ansgar; Herbert-Maul, Annika; Sauter, Alexandra; Linder, Stephanie; Till, Maike (Frontiers in Public Health, 2021)
Introduction: Community-based participatory research (CBPR) is considered to be of high potential for health promotion among socially disadvantaged groups. However, the long-term implementation and transfer of these approaches remain challenging, and the public health impact they achieve is difficult to study. This also pertains to the potential health effects and cost-effectiveness of CBPR. This study protocol describes the follow-up case study (NU-BIG) after 15 years of the BIG project (“movement as investment in health”), a project to promote physical activity among socially disadvantaged women. Through a participatory approach BIG empowers the adressed women to plan and implement low-thresholf physical activity offers. Since the project started in 2005 it was transferred to 17 communities in Germany. Materials and Analysis: NU-BIG intends to examine the long-term effects, including economic aspects, of the BIG project on individual and structural levels at all project sites as well as it’s long-term implementation and transfer. NU-BIG is a cross-sectional and longitudinal study using a mixed method approach. For the longitudinal section, we re-analyse existing data from former BIG evaluations. For cross-sectional data collection we use questionnaires and conduct qualitative interviews and focus groups. Women who take part in BIG programme offers are part of the research team and will use the photo-voice approach to report on the effects of BIG. The study population consists of about 800 women who participate in BIG project offers and 50 persons involved in the implementation of the BIG project at local sites. Discussion: The expected results from NU-BIG are highly relevant for studying the long-term public health impact of CBPR. In particular, this project intends to answer questions on how the transfer of such projects can succeed and which factors determine if a CBPR project can be sustained at the community level. Eventually these results can contribute to the further development of participatory approaches to provide effective health promotion among socially disadvantaged groups.<br
Keywords: long-term public health impact; physical activity; Community-Based Participatory Research; low socioeconomic status; Ethnic Minorities; Vulnerable groups

Transferring a community-based participatory research project to promote physical activity among socially disadvantaged women -Experiences from 15 years of BIG - Herbert-Maul, Annika; Abu-Omar, Karim; Frahsa, Annika; Streber, Anna; Reimers, Anne Kerstin (Frontiers in Public Health, 2020)